Захист працюючих від електромагнітного випромінювання під час роботи з ПК - Дзюндзюк, Б. В.; Хондак, І. І.; Березуцька, Наталія Львівна (НТУ "ХПІ", 2009)
Работа посвящена защите работников, использующих компьютерные и информационные технологии от электромагнитного излучения, а также рациональному размещению рабочих мест в помещении с персональными компьютерами. Эта работа может использоваться и как обучающая в учебном процессе университетов на факультетах компьютерных и информационных технологий

Work is devoted to defence of working of computer and informative technologies from the electromagnetic radiation, and also rational placing of workplaces in the apartment with the personal computers. This work can be used and as educational in the educational process of universities on the faculties of users of computer and informative technologies.
Keywords: ЕМВ; нормативно-правова інформація; охорона праці; генератор; робочі місця